Targeting Lipid Rafts as a Strategy Against Coronavirus - Sorice, Maurizio; Misasi, Roberta; Riitano, Gloria; Manganelli, Valeria; Martellucci, Stefano; Longo, Agostina; Garofalo, Tina; Mattei, Vincenzo (Frontiers in Cell and Developmental Biology, 2021)
Lipid rafts are functional membrane microdomains containing sphingolipids, including gangliosides, and cholesterol. These regions are characterized by highly ordered and tightly packed lipid molecules. Several studies revealed that lipid rafts are involved in life cycle of different viruses, including coronaviruses. Among these, recently emerged the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The main receptor for SARS-CoV-2 is represented by the angiotensin-converting enzyme-2 (ACE-2), although it also binds to sialic acids linked to host cell surface gangliosides. A new type of ganglioside-binding domain within the N-terminal portion of the SARS-CoV-2 spike protein was identified. Lipid rafts provide a suitable platform able to concentrate ACE-2 receptor on host cell membranes where they may interact with the spike protein on viral envelope. This review is focused on selective targeting lipid rafts components as a strategy against coronavirus. Indeed, cholesterol-binding agents, including statins or methyl-β-cyclodextrin (MβCD), can affect cholesterol, causing disruption of lipid rafts, consequently impairing coronavirus adhesion and binding. Moreover, these compounds can block downstream key molecules in virus infectivity, reducing the levels of proinflammatory molecules (TNF-α, IL-6) and/or affecting the autophagic process involved in both viral replication and clearance. Furthermore, cyclodextrins can assemble into complexes with various drugs to form host-guest inclusions and may be used as pharmaceutical excipients of antiviral compounds, such as lopinavir and remdesivir, by improving bioavailability and solubility. In conclusion, the role of lipid rafts-affecting drugs in the process of coronavirus entry into the host cells prompts to introduce a new potential task in the pharmacological approach against coronavirus.